Hubungan Kreativitas Guru dan Lingkungan Belajar dengan Minat Belajar IPS di SDN Pinangsia Tamansari - Rustimah, Siti; Amaliyah, Nurrohmatul; Sukardi, Edy (AR-RIAYAH: Jurnal Pendidikan Dasar, 2023)
Each student's ability to understand lessons is different, where teachers often see students facing learning difficulties caused by various things. So, the aim of this research is to understand students' interest in learning which is linked to teacher creativity or the learning environment. Correlational quantitative is used as the approach for this research. This research had a population of class V students in 3 schools, with random sampling techniques and 126 students as research samples, as well as questionnaires and documentation as data collection techniques. The results of this research (1) directly show a positive relationship between creative teachers and students' interest in learning, meaning that better teacher creativity can also increase students' interest in learning. (2) the positive relationship between the learning environment and student interest in learning, meaning that if the learning environment improves, student interest in learning also tends to improve as well. (3) a positive direct relationship between creative teachers and the learning environment and student interest in learning. This means that if creative teachers and students' learning environment are considered together, this will lead to an increase in students' interest in learning.